Acetyl‐CoA Carboxylase Inhibition Reverses NAFLD and Hepatic Insulin Resistance but Promotes Hypertriglyceridemia in Rodents. Issue 6 (29th November 2018) - Goedeke, Leigh; Bates, Jamie; Vatner, Daniel F.; Perry, Rachel J.; Wang, Ting; Ramirez, Ricardo; Li, Li; Ellis, Matthew W.; Zhang, Dongyan; Wong, Kari E.; Beysen, Carine; Cline, Gary W.; et al.
Abstract : Pharmacologic inhibition of acetyl‐CoA carboxylase (ACC) enzymes, ACC1 and ACC2, offers an attractive therapeutic strategy for nonalcoholic fatty liver disease (NAFLD) through simultaneous inhibition of fatty acid synthesis and stimulation of fatty acid oxidation. However, the effects of ACC inhibition on hepatic mitochondrial oxidation, anaplerosis, and ketogenesis in vivo are unknown. Here, we evaluated the effect of a liver‐directed allosteric inhibitor of ACC1 and ACC2 (Compound 1) on these parameters, as well as glucose and lipid metabolism, in control and diet‐induced rodent models of NAFLD. Oral administration of Compound 1 preferentially inhibited ACC enzymatic activity in the liver, reduced hepatic malonyl‐CoA levels, and enhanced hepatic ketogenesis by 50%. Furthermore, administration for 6 days to high‐fructose‐fed rats resulted in a 20% reduction in hepatic de novo lipogenesis. Importantly, long‐term treatment (21 days) significantly reduced high‐fat sucrose diet–induced hepatic steatosis, protein kinase C epsilon activation, and hepatic insulin resistance. ACCi treatment was associated with a significant increase in plasma triglycerides (approximately 30% to 130%, depending on the length of fasting). ACCi‐mediated hypertriglyceridemia could be attributed to approximately a 15% increase in hepatic very low‐density lipoprotein production and approximately a 20% reduction in triglyceride clearance by lipoprotein lipase ( P  ≤ 0.05). At the molecular level, these changes were associated with increases in liver X receptor/sterol response element‐binding protein‐1 and decreases in peroxisome proliferator–activated receptor‐α target activation and could be reversed with fenofibrate co‐treatment in a high‐fat diet mouse model. Conclusion: Collectively, these studies warrant further investigation into the therapeutic utility of liver‐directed ACC inhibition for the treatment of NAFLD and hepatic insulin resistance.